106k views
5 votes
Solve for x. 3 x−1 = 9 x+2

2 Answers

0 votes

Answer:

x = -1/2

Explanation:

Given equation,

→ 3x - 1 = 9x + 2

Now we have to,

→ Find the required value of x.

Then the value of x will be,

→ 3x - 1 = 9x + 2

Rearrange in order of like terms:

→ 3x - 9x = 2 + 1

→ -6x = 3

Divide the RHS with number (-6):

→ x = 3/(-6)

→ x = -3/6

→ [ x = -1/2 ]

Hence, the value of x is -1/2.

User Will Ray
by
5.2k points
7 votes

3x − 1 = 9x +2

3x = 9x + 3

-6x = 3

x = -1/2

Hope this helps! ;)

User XRed
by
5.6k points